A holistic intervention program for children from low socioeconomic status families - TANG, Jonathan S. E. (Institutional Knowledge at Singapore Management University, 2014)
There is considerable evidence that children from families with low socioeconomic status (SES) are at risk of profound delays in cognitive development and educational achievement. Scholars and policy makers have therefore sought to identify the potential causes of these problems and to design interventions to narrow this achievement gap. With this goal, Neville et al. (2013) developed a family-based intervention (PCMC-A) to improve neurocognitive functions supporting selective attention in low-SES preschoolers. Involving both parents and children in the training, they demonstrated that the PCMC-A significantly improved nonverbal IQ, receptive language, neurocognitive functions supporting early attentional processing, parent-reported social skills, and parent-child interactions, and reduced parenting stress. Given that previous studies have focused on the training of children, it is noteworthy that Neville et al. examined factors related to not only children but also parents (e.g., parents' stress regulation and contingency-based discipline) and the home environment (e.g., parent-child interaction, parents' language use with the child, and facilitation of child attention).